Keller resection arthroplasty - Viladot Voegeli, Antonio; Nuñez-Samper, Mariano (Journal of the Foot & Ankle, 2022)
The resection arthroplasty first described by Keller for hallux valgus has subsequently been applied to treat hallux rigidus. Some variations to the original procedure have been described, such as the interposition of soft tissue in the resection area (joint capsule, tendon, etc.), as a spacer, in order to reduce the amount of phalanx to be resected and improve stability and mobility. Another procedure, proposed by Valente Valenti, consists of performing a “V” shaped arthrectomy in the sagittal plane, at the level of the metatarsal and the phalanx. We are faithful to the original technique, resecting approximately one third of the phalangeal base and the periarticular osteophytes, seeking for the correct balance between the flexor and extensor muscles of the hallux. Resection arthroplasty is indicated in stage III or in stage III-IV of the Regnauld and Coughlin and Shurnas classifications, respectively. Both in our own experience and when reviewing the bibliography, we find that very acceptable results are obtained. Level of Evidence V; Therapeutic Studies; Expert Opinion.